β-Cyclodextrin-Mediated Acetic Acid Catalyzed Diastereoselective Mannich Reaction in Water - Sukumari, Subbiah; Azath, Ismail Abulkalam; Pitchumani, Kasi (Synlett, 2012)
A highly efficient diastereoselective Mannich reaction has been carried out in water using a catalytic amount of β-cyclodextrin as a chiral host in the presence of acetic acid to give the corresponding β-aminoketones (Mannich bases) with good yield (up to 98%) and excellent diastereomeric excess (up to >99%). This Brønsted acid–chiral cyclodextrin composite catalyzed reaction proceeds in a syn-selective manner with 98:2 syn/anti selectivity when propiophenone is used as the ketone moiety and in an anti-selective manner with 100:0 (anti/syn) selectivity when cyclohexanone is used.
Keywords: mannich bases; diastereoselectivity; cyclodextrins; aqueous medium; supramolecular chemistry